The dynamics between internationalization strategies and innovative performance within ICT companies - Ximenes, Polyana Karina Mendes; Cabral, José Ednilson de Oliveira; Tassigny, Mônica Mota; Câmara, Samuel Façanha; Tavares, Jessie Coutinho de Souza (Revista de Administração da UFSM, 2020)
The article aims to evaluate the existence of a coevolution between internationalization strategies and innovative performance within information and communication technology (ICT) companies located in the northeast of Brazil. In order to achieve this objective, a conceptual model was derived from the literature review contemplating the vision that internationalization and innovation within companies happen in an evolutionary and dynamic way. Methodologically, the study is characterized by being qualitative, using the technique of multiple cases. The studied companies (IVIA, IFACTORY, CPQI and GREENMILE) presented changes in both internal and external competences. Thus, a main conclusion has been that the studied companies presented a process of coevolution between innovation and internationalization strategies. In terms of business strategies, it can be verified that the presence of these two processes, guarantees the development and growth of companies in the global market.